Albania : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for a Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2004)
The economy has thus far been fairly resilient to recent political uncertainties, although the reform process has been adversely affected. Continued growth will depend to a large extent on higher private investment, which will require further improvements in governance and the implementation of reform. The combination of a better investment climate and sound fiscal management is essential for ensuring external viability. Monetary policy has been successful, but rapid changes in the financial system call for continued vigilance. Program implementation has been uneven, but satisfactory.